O princípio da razoável duração do processo nas reformas processuais e as garantias do acesso à Justiça, contraditório e ampla defesa - Camacho, Luciana da Silva Paggiatto (2015)
This study aims to analyse the principle of reasonable duration of proceedings in relation to procedural reforms guarantees of access to justice, contradictory and full defense. If you live in times in which anxiety is the storm of modern society. Seeks to produce several activities simultaneously both domestic and professional; there is a plurality of activities execution and interpersonal relationships in short periods of time. So there is also the impact of this dynamic law, and therefore would not be different under the process, now more than ever it seeks to build mechanism to make the process quicker meeting the expectations of society. The objectives pursued in this work, briefly, are: (a) conceptualize principle; (b) conceptualize the principles of reasonable duration of proceedings, access to justice, contradictory and full defense; and (c) discuss the recent procedural reforms as well as on the Draft Code of Civil Procedure. As said, the topic is of paramount importance in view of all legislative reforms in the civil case and the impending enactment of a new Code of Civil Procedure, which seeks to clearly bring more promptness in support of the constitutional principle of reasonable duration of the process and bring greater effectiveness judgments. So work on screen, has the ultimate goal collate the principle of reasonable duration of the process with other basic principles and guarantees: access to justice, contradictory and full defense on an analysis of mitigation latest fundamental guarantees in the recent reforms in the speed allowance procedural